2020
DOI: 10.4314/njt.v39i1.24
|View full text |Cite
|
Sign up to set email alerts
|

Single user TCP downstream throughput probability models in IEEE802.11b WLAN system

Abstract: Single User, Transmission Control Protocol Downstream Throughput (TCPDST) probability models in an IEEE802.11b WLAN have been developed, validated and evaluated for performance. Measurement of single user TCPDST were taken using Tamosoft throughput test while that of signal to noise ratio (SNR) were taken using inSSIDer 2.1. The Tamosoft throughput tests were conducted using different quality of service (QoS) traffic. These QoS traffic (which were sent through an infrastructure based network) correspond to dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…But on the average, it could be said that the plot shows a slowly increasing jitter with time. The findings here are in total agreement with [13,16].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…But on the average, it could be said that the plot shows a slowly increasing jitter with time. The findings here are in total agreement with [13,16].…”
Section: Resultssupporting
confidence: 93%
“…Their results showed that 1EEE 802.11p performed better. A two types of single user models was developed in [16] for predicting transmission control protocol (TCP) downstream throughput in IEEE 802.11g wireless local area networks, for different signal to noise ratio (SNR) categories. They used Tamosoft throughput test tool to collect different SNRs in open corridor, free space and small offices.…”
Section: Review Of Past Workmentioning
confidence: 99%
“…The work done by [7], used NETSIM for simulation and analysis of LAN network performance implemented in CIT college campus network for realistic traffic scenarios and to study its performance metrics. In [8], empirical probability models for predicting TCP downstream throughput in WLAN system were presented. The paper contains information indicating the dependence of TCP downstream on SNR for various observed signal levels.…”
Section: Related Workmentioning
confidence: 99%
“…Papers on measuring and investigating TCP upstream dependence on SNR models that could predict TCP performance at various signal ranges and environments have been investigated. The investigations at real network time were done for IEEE 802.11b systems and the outcome indicates its importance as a tool in WLAN deployment as [developed in [8][9][10] [11]. The work done in [12], used UDP traffic to measure uplink and downlink signal strength from a network interface Card while monitoring the packet error rate at the data link layer and the throughput at the transport layer.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation